Please view the picture and answer this question urgent
Attachments:
![](https://hi-static.z-dn.net/files/d05/6d309e7b2ebac54b72c22c0e0f62f116.jpg)
Answers
Answered by
1
Use identity,
Answered by
1
by formula
a3+b3+c3-3abc= (a+b+c)(a2+b2+c2-ab-bc-ca)
u need the value of a2+b2+c2
a2+b2+c2=(a+b+c)squ-2(ab+bc+ca)
hence a2+b2+c2=4
now putting value
4(4-6)
=4×-2
=-8
hence proved
a3+b3+c3-3abc= (a+b+c)(a2+b2+c2-ab-bc-ca)
u need the value of a2+b2+c2
a2+b2+c2=(a+b+c)squ-2(ab+bc+ca)
hence a2+b2+c2=4
now putting value
4(4-6)
=4×-2
=-8
hence proved
Similar questions